2004
DOI: 10.1186/1471-2458-4-18
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of delays amongst pulmonary tuberculosis patients in Lagos, Nigeria

Abstract: Background: Pulmonary tuberculosis continues to increase due to late patient presentation. The study was conducted at a chest clinic of a general hospital in Lagos, Nigeria, to investigate patterns of delays before treatment amongst tuberculosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
88
7
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 5 publications
(10 reference statements)
23
88
7
2
Order By: Relevance
“…This calls for the promotion of health education that stresses on the correct causes of TB, and ways to reduce stigma and discrimination. Stigma and discrimination of TB patients was also found to influence delay in the seeking of treatment in Nigeria (Odusanya & Babafemi, 2004). Studies from elsewhere have shown that relatives and neighbours mistreated TB patients in fear of catching the disease (Somerville & Orkin, 1989;Steen & Mazonde, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This calls for the promotion of health education that stresses on the correct causes of TB, and ways to reduce stigma and discrimination. Stigma and discrimination of TB patients was also found to influence delay in the seeking of treatment in Nigeria (Odusanya & Babafemi, 2004). Studies from elsewhere have shown that relatives and neighbours mistreated TB patients in fear of catching the disease (Somerville & Orkin, 1989;Steen & Mazonde, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, the probability that tuberculosis patients are likely to be infected with HIV is high as perceived by the community in our study area. In Tanzania, statistics indicate that between 32-44% of TB patients are also HIV infected (Range, et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delays in diagnosis and treatment of TB cases are major impeding factors in the control of TB. A single infectious person who remains untreated can infect between ten and fifteen people every year, spreading the infection in the community 1,2 . In addition, delayed TB diagnosis and treatment may result in more extensive disease and more complications, and increases the risk of mortality 3,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The most common potential reason for patient delay is the neglect of symptoms by the patient. A low index of suspicion for tuberculosis is an important reason for doctor delays (10,19,20,22,37). An assessment of the response to antibiotic therapy is a common approach in patients with pulmonary symptoms and abnormal chest x-ray findings, which may result in doctor delays (18,38).…”
Section: Reasons For Delaysmentioning
confidence: 99%